Suggestions for Post-Pandemic Economic Recovery Research Agenda in Islamic Entrepreneurship - Cahyani, Utari Evy; Siregar, Rizal Ma'ruf Amidy (El-Barka, 2022)
Introduction/Main Objectives: The concept of Islamic entrepreneurship began to develop in line with the development of Islamic economics. This study aims to provide a bibliometric analysis of the scope of Islamic entrepreneurship. Background Problems: The existence of a pandemic has caused entrepreneurs to have to adapt to a volatile, complex, and uncertain business environment. Entrepreneurs also have homework to do, which is related to economic recovery after the pandemic. Novelty: Presenting bibliometric analysis and identifying publication trends in the scope of Islamic entrepreneurship in Scopus indexed journals from 2009 to 2022. Research Methods: This study uses descriptive statistics based on 78 published articles related to Islamic entrepreneurship. The articles used journal articles, conference papers, and book sections indexed by Scopus. Data was collected by Publish or Perish which was then analyzed using VOSviewer and Excel. Finding/Results: The results show the journals that contain the most articles on Islamic entrepreneurship are The International Journal of Business and Globalization. The most cited article is “The context of Islamic entrepreneurship and business: Concepts, principles, and perspectives”. The author who has written the most about Islamic entrepreneurship is Veland Ramadani. In research on Islamic entrepreneurship, the word “entrepreneurship” is the most widely used keyword. Recent research related to Islamic entrepreneurship is related to economic growth, business innovation, SME innovation, knowledge, and socio-cultural. Conclusion: This research helps researchers determine their research position, find potential themes for future research and provide recommendations to policymakers for post-pandemic economic recovery.